THE EFFECT OF USING AUTHENTIC MATERIALS ON READING COMPREHENSION ACROSS SECONDARY STUDENT’ COGNITIVE LEARNING STYLE - Noor Aisyah; Aulia Azmi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The teaching of reading nowadays is urged to empower students to cope with 21st century literacy challenges and to develop prevailing 21st century. Further, English teachers have to implement interesting and creative materials and strategies to motivate students in learning English. Compared to non-authentic materials, authentic materials seemed more promising to fulfill the demand. The aim of this study was to investigate whether or not the use of authentic materials in the classroom in teaching reading comprehension is effective toward students’ cognitive learning styles. The effect of authentic materials was compared to the non-authentic ones. This study employed a quasi-factorial 2 x 2 design and involved 68 tenth graders SMKN 3 Banjarmasin, South Kalimantan Province. The instruments used were reading comprehension posttest and GEFT. Statistical analysis was performed using SPSS 23.0 to test hypotheses at .05 level of significance. The results showed that authentic materials improved students’ reading comprehension compared to the non-authentic ones. It conforms to the theory of authentic materials and the previous studies indicating authentic material is effective in improving students’ reading comprehension. It was further found that there was no significant difference in the reading comprehension between field independent and field dependent students. Based on the results, it can be concluded that using authentic materials is promising alternative materials to help students increase students’ reading comprehension with different cognitive learning styles.